Quantitative Frameworks for Investigating the Relationships Between Sustainability Factors and Lifelong Learning - Nagy-Rádli, Dalma; Bódizs, Dalma; Zseni, Anikó (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In an era characterized by rapid economic growth, globalization, and pressing environmental challenges, the role of education in advancing sustainability has become paramount. This paper's primary focus is on sustainability, aiming to provide meaningful insights into the function of educational attainment, specifically lifelong learning, in promoting sustainable development. The paper's novel approach lies in its data-driven perspective, utilizing international indices to quantify the relationship between educational metrics and the UN Sustainable Development Goals. This paper adopts a quantitative, index-based methodology to compare lifelong learning performance across four countries with similar economic circumstances, utilizing sustainability indicators from the SDG Index, Youth Progress Index, and Social Progress Index. The key findings reveal that while Estonia exhibited leading performance, Hungary's index value declined between 2016 and 2022. In contrast, Turkey demonstrated the most substantial improvement during this period, despite starting from the lowest point. The paper emphasizes the importance of carefully managing educational incentives and innovations to strengthen the alignment between sustainability and lifelong learning, particularly in addressing specific sustainability challenges through targeted ESG strategies.